2019
DOI: 10.1039/c8ta10631b
|View full text |Cite
|
Sign up to set email alerts
|

Efficient catalytic conversion of terminal/internal epoxides to cyclic carbonates by porous Co(ii) MOF under ambient conditions: structure–property correlation and computational studies

Abstract: Efficient CO2 capture/utilization by Co(ii) MOF as a heterogeneous catalyst in CO2–epoxide cycloaddition at ambient condition has been investigated and correlated with computational studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 102 publications
2
68
0
Order By: Relevance
“…Furthermore, the described observations clearly demonstrate the role of an acylhydrazone in the proposed catalytic mechanism for CO 2 cycloaddition that leads to terminal/internal epoxides, as described by Suresh and co-workers ( Figure S13 ). 40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the described observations clearly demonstrate the role of an acylhydrazone in the proposed catalytic mechanism for CO 2 cycloaddition that leads to terminal/internal epoxides, as described by Suresh and co-workers ( Figure S13 ). 40 …”
Section: Resultsmentioning
confidence: 99%
“… 24 In situ PXRD provides global information about two-step structural transformation, while in situ IR and NMR shed light on the interaction between carbon dioxide and acylhydrazone group (−C(O)=N–NH−). 39 , 40 Moreover, one-component (CO 2 , CH 4 , Ar, O 2 , and N 2 ) and multicomponent (CH 4 /CO 2 ) equilibrium adsorption studies in a broad temperature range have shown high selectivity of JUK-8 toward carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…The excellent catalytic activity of HbMOF 1 for cycloaddition of various terminal epoxides motivated us to study the catalytic activity for the cycloaddition of internal epoxides, which are known to be less reactive than the terminal epoxides [15b, 22, 23] . Therefore, normally higher reaction temperature and/or pressure with prolonged reaction time are employed for the conversion of internal epoxides [15b, 22–24] . On the contrary, our catalyst HbMOF 1 catalyzes the cycloaddition of cyclopentene oxide (CPO) to the corresponding cyclic carbonate with about 70 % conversion with a turnover number (TON) of 700 under mild reaction conditions (1 bar CO 2 and RT; Table 1 and Figure S25).…”
Section: Resultsmentioning
confidence: 99%
“…The difference between the relative energies of TS‐1 and IC as shown in Scheme 2 is 9.6 kcal mol −1 . Also, this energy barrier for the ring‐opening step is treated as the rate‐determining step in the CO 2 fixation with PO according to several other previously reported DFT energy profiles for cycloaddition reactions [15b, 27] . Next, the CO 2 insertion to the bromide‐substituted alkoxide species in TS‐1 occurs with a relative energy of 24.6 kcal mol −1 as the cycloaddition progresses.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Additionally, the selective coupling between CO 2 and epoxides to produce cyclic carbonates has also attracted significant attention in this area because of its wide applications (Scheme 1). [13][14][15][16][17][18][19][20][21][22][23][24][25] However, the use of catalysts and co-catalysts under low temperature and pressure conditions is challenging for the cycloaddition reactions. One solution is to design catalytic systems that can easily attract and activate CO 2 , which will allow them to be used at low reaction temperatures and ambient pressures.…”
Section: Introductionmentioning
confidence: 99%